Cloudemy: Step into the Cloud - Mohd. Nor, Rizal; Mohamed Razi, Mohamed Jalaldeen; Adlan Arif, Zakaria; Ahmad Safiuddin, Ahmad Fakhri; Puteri Zulaiha, Abdul Saat (Universiti Teknikal Malaysia Melaka, 2017)
Cloud computing is often referred to as a general term for the delivery of hosted services over the Internet, providing users choices among less expensive computing services in terms of user-friendliness, accessibility, and reliability. Thanks to the rapid advancement of technology today, the growth of cloud computing has boomed. However, existing cloud computing platforms and services are too costly for educational institutions to use, and proper platforms that utilize the current services are scarce. In this paper, a prototype cloud service called Cloudemy is developed to provide an affordable cloud service to meet the education needs. Cloudemy utilizes the Openstack framework coupled with a customized attractive web panel for users to interact with the system. Cloudemy allows users to deploy their own servers and make use of the resources at an affordable price all according to their chosen plan and within the scope of teaching and learning. The main contribution of this research work is to provide educational support for students to engage in cloud computing through the use of tutorials and documentations within the cloud platform.